A qualitative study of women’s perspectives on postnatal depression in Malaysia - Mohd Arifin, Siti Roshaidai; Cheyne, Helen; Maxwell, Margaret (2015)
Background: Postpartum depression (PND) is considered as a significant health problem and gained special attention due to women’s vulnerability during childbearing years, highly associated with suicide and its negative impacts on women, child, family and society. Despite these concerns, PND has still remains underdiagnosed and undertreated in the clinical practice. Previous studies suggest that sociocultural context of motherhood have a link with PND and that treatment of PND should be culturally appropriate, yet there was no research on the Malaysian women’s experience of PND have been published up to this date. Objectives: The aims of this study are to: i) explore postnatal women’s perceptions of PND in Malaysia, ii) understand the experience of PND among postnatal women in Malaysia, and iii) explore potential interventions for women with PND in Malaysia. Method: This study employs an exploratory qualitative design. The critical realism is considered as the philosophical framework underpinning the study. A total of 34 women with different Malaysian cultural backgrounds who attend for postnatal care and/or child immunization at eight selected Maternal and Child Health (MCH) Clinics in Kuala Lumpur were recruited. The women were screened for postnatal depressive symptoms using The Patient Health Questionnaire-2 (PHQ-2) and Edinburgh Postnatal Depression Scale (EPDS). Those who score three or more in PHQ-2 and/or 12 or more in EPDS have been invited for the interview session. The face to face semi structured interviews have been used to explore the women’s perspectives of PND. Data collection and data analysis were conducted concurrently. Data will be analysed using deductive thematic analysis (framework method). Nvivo, a software package will be used to develop coding on each transcript. Conclusion: This study will add on the theoretical concepts of PND and its relation to cultural background through understanding and exploration of PND experience from Malaysian perspectives. It will also encourage further high quality work to provide effective, relevant and culturally sensitive intervention for PND. The findings of this study will be the foundation of developing preventative intervention for PND in Malaysia.